1984
DOI: 10.1063/1.94853
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between background carrier concentration and x-ray linewidth for InGaAs/InP grown by vapor phase epitaxy

Abstract: The background carrier concentration of nominally undoped InGaAs/InP grown by the hydride process was found to correlate to the x-ray linewidth. A double crystal diffractometer was used to measure the mismatch parallel to the (100) surface as well as the more standard perpendicular mismatch. The epitaxial layers were, in general, found to be tetragonally distorted, and the linewidth was found to correlate to the parallel mismatch. Two regimes for the carrier concentration were identified, one for samples havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It has been reported that nonequilibrium conditions achieved with Molecular Beam Epitaxy (MBE) generally lead to experimental critical thickness which are very much dependent on the growth conditions [2,3]. Macrander et.al [11] gave a correlation between the carrier concentration and the X-ray line widths for InGaAs/InP. Metal Organic Chemical Vapor Deposition (MOCVD) grown InGaAs/InP structures have also been studied using various characterization techniques to understand the mismatch strain on the bandgap [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nonequilibrium conditions achieved with Molecular Beam Epitaxy (MBE) generally lead to experimental critical thickness which are very much dependent on the growth conditions [2,3]. Macrander et.al [11] gave a correlation between the carrier concentration and the X-ray line widths for InGaAs/InP. Metal Organic Chemical Vapor Deposition (MOCVD) grown InGaAs/InP structures have also been studied using various characterization techniques to understand the mismatch strain on the bandgap [5].…”
Section: Introductionmentioning
confidence: 99%